Contrasting impacts of land‐use change on phylogenetic and functional diversity of tropical forest birds. Issue 4 (16th January 2018) - Chapman, Philip M.; Tobias, Joseph A.; Edwards, David P.; Davies, Richard G.
Abstract: Biodiversity conservation strategies increasingly target maintaining evolutionary history and the resilience of ecosystem function, not just species richness (SR). This has led to the emergence of two metrics commonly proposed as tools for decision making: phylogenetic diversity (PD) and functional diversity (FD). Yet, the extent to which they are interchangeable remains poorly understood. We explore shifts in and relationships between FD and PD of bird communities across a disturbance gradient in Borneo, from old‐growth tropical forest to oil palm plantation. We show a marked decline in PD, and an increase in phylogenetic mean nearest taxon distance from forest to oil palm, in line with declining SR across the gradient. However, phylogenetic mean pairwise distance is constrained by forest logging more than by conversion to oil palm, taking account of SR. The decline in FD across the gradient is less severe than in PD, with all metrics indicating relatively high trait diversity in oil palm despite low SR, although functional redundancy is much reduced. Accounting for SR, levels of functional over‐ or under‐dispersion of bird communities are strongly coupled to habitat disturbance level rather than to any equivalent phylogenetic metric. Policy implications . We suggest that while phylogenetic diversity (PD) is an improvement on species richness as a proxy for functional diversity (FD), conservation decisions based on phylogenetic diversity alone cannot reliably safeguard maximal functional diversity. Thus, phylogenetic diversity and functional diversity are related but still complementary. Priority setting exercises should use these metrics in combination to identify conservation targets.